2012
DOI: 10.1124/dmd.111.043158
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Cytochrome P450-Mediated Drug-Drug Interactions Using Cryopreserved Human Hepatocytes: Comparison of Plasma and Protein-Free Media Incubation Conditions

Abstract: ABSTRACT:Cryopreserved human hepatocytes suspended in human plasma (HHSHP) have previously provided accurate CYP3A drug-drug interaction (DDI) predictions from a single IC 50 that captures both reversible and time-dependent inhibition. The goal of this study was to compare the accuracy of DDI predictions by a protein-free human hepatocyte system combined with the fraction unbound in plasma for inhibitor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…Generally, the known CYP3A inhibitors showed a less potent TDI in HEP relative to HLM, which have yielded an impact on the in vivo DDI prediction (Xu et al, 2009;Chen et al, 2011;Kirby et al, 2011). Furthermore, it has been reported that cryopreserved human hepatocytes suspended in human plasma (HSP), compared with those in protein-free media, showed better DDI predictions for some of cytochrome P450 inhibitors (Mao et al, 2011(Mao et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the known CYP3A inhibitors showed a less potent TDI in HEP relative to HLM, which have yielded an impact on the in vivo DDI prediction (Xu et al, 2009;Chen et al, 2011;Kirby et al, 2011). Furthermore, it has been reported that cryopreserved human hepatocytes suspended in human plasma (HSP), compared with those in protein-free media, showed better DDI predictions for some of cytochrome P450 inhibitors (Mao et al, 2011(Mao et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic approach is increasingly being employed in drug discovery and development setting to predict pharmacokinetics (PK) and DDI potential in the clinic. Traditionally, DDI predictions have been performed with static mathematical models using various inhibitor concentrations such as hepatic inlet or outlet concentrations in total (protein bound plus unbound) or unbound form (Mayhew et al, 2000;Obach et al, 2007;Fahmi et al, 2009;Boulenc and Barberan, 2011;Mao et al, 2012). In these reports, hepatic DDI magnitudes for RI were reasonably predicted using the projected unbound portal vein (or hepatic inlet) concentration (C inlet,u ), whereas the use of unbound systemic (or hepatic outlet) concentration (C sys,u ) yielded better prediction for TDI and EI compared with C inlet,u .…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported approaches have employed a static model that requires [I] as a parameter and they are not practical in early phase drug discovery, in which information for [I] is lacking. Although [I] would become accessible surrogates in late phase drug discovery, several investigators used different [I] for DDI prediction (Lu et al, 2006(Lu et al, , 2008Mao et al, 2011Mao et al, , 2012Shibata et al, 2008). Thus, it has not been clarified which inhibitor concentration is appropriate in the use of hepatocytes suspended in serum/plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The majority were below a 5 times interaction factor (multiplier) (USEPA 2000b(USEPA , 2003. The U.S. Food and Drug Administration (USFDA) has draft guidelines for running pharmaceutical interaction studies based on a comparisons of enzyme induction potentials and clinical pharmacokinetics (USFDA 2012; Mao et al 2011Mao et al , 2012. In Table 2 the USFDA categories and their associated increases in internal exposure as AUC or "area under the curve" from clinical samples.…”
Section: Range Of Interaction Valuesmentioning
confidence: 99%
“…The "Comments" column has a "Default," where the group default value is used, from Table 2, when definite DDI values cannot be determined based on the USFDA categories (Mao et al 2011(Mao et al , 2012. If two pharmaceuticals are not documented having interactions based on the data available, the pair is not included in Table 3.…”
Section: Range Of Interaction Valuesmentioning
confidence: 99%